2014
DOI: 10.1111/pme.12332
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Knowledge of Health Care Professionals About Pain Management and Use of Opioids in Pediatrics

Abstract: Problems in the processes of pain identification, measurement, and treatment have been found. Results suggest that there is a need for both an investment in continuing education of professionals and the development of protocols to optimize the analgesic therapy, thus preventing increased child suffering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
2
28
4
Order By: Relevance
“…This variation was also noticed by other conducted studies [21, 23, 35, 41, 50] and could be due to inadequate educational curriculum and insufficient clinical training programs [23, 26, 44, 51]. …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This variation was also noticed by other conducted studies [21, 23, 35, 41, 50] and could be due to inadequate educational curriculum and insufficient clinical training programs [23, 26, 44, 51]. …”
Section: Discussionsupporting
confidence: 59%
“…HCPs' correct answer rate to questions related to this group of patients was the lowest. Likewise other studies described the ill preparation of HCPs to assess and manage children's pain [15, 16, 27, 50, 54, 55]. …”
Section: Discussionmentioning
confidence: 99%
“…A review of pain assessment in elderly patients with dementia demonstrated that the Pain Assessment Checklist for Seniors with Limited Ability to Communicate, a 4-dimension checklist measuring facial expression, body movement, mood, and physiological signs, provided the greatest sensitivity and utility among the 12 assessment scales reviewed [79]. However, these techniques are underutilized in the ED for pediatric and elderly patients [14,80,81], who are at increased risk of undertreatment of pain, despite pain assessment for all hospital patients being a mandatory component of standard care outlined by The Joint Commission [82].…”
Section: New Therapeutic Options For the Management Of Acute Painmentioning
confidence: 97%
“…Acupuncture is a viable alternative for the treatment and management of acute and chronic pain across various illnesses [22,103,113,114,115]. One overview of Cochrane reviews concluded that acupuncture demonstrates effectiveness as a treatment for pain associated with migraines, tension headaches, neck disorders, arthritis, and low back pain [104].…”
Section: The Mind–body Approach To Painmentioning
confidence: 99%